Reducing Data Deficiencies: Preliminary Elasmobranch Fisheries Surveys in India, Identify Range Extensions and Large Proportions of Female and Juvenile Landings - Johri, Shaili; Livingston, Isabella; Tiwari, Anjani; Solanki, Jitesh; Busch, Anissa; Moreno, Isabel; R. Fellows, Sam; Doane, Michael P.; Dinsdale, Elizabeth A. (Frontiers in Marine Science, 2021)
Chondrichthyes, an ancient and diverse class of vertebrates, are crucial to the health of marine ecosystems. Excessive demand for chondrichthyan products has increased fishing pressure, threatening ∼30% of species with extinction in recent decades. India is the second-largest shark landing nation globally and the province of Gujarat, is the largest contributor to its shark exports. Despite their significant contribution to global fish supplies, chondrichthyan fisheries in Gujarat remain understudied and many species, data deficient, posing challenges to the conservation of remaining populations in the region. Here, we report results from taxonomic assessment of elasmobranchs at four key landing sites in Gujarat. We identified thirty-one species of sharks and rays with a significant bias toward capture of females and juveniles by fisheries. Our data indicate the presence of nursery areas for species such as Sphyrna lewini and Rhynchobatus laevis in the neritic areas off Gujarat. Further, we discovered extensions of the current distribution range for three species -Torpedo sinuspersici, Carcharhinus sorrah, and Rhinobatos punctifer. Taxonomic identities for a subset of species were confirmed using genomic analyses conducted with portable DNA sequencing tools. We present assessments for six data deficient species in the region – Rhinobatos annandalei, Rhinoptera jayakari, Maculabatis bineeshi, Pateobatis bleekeri, T. sinuspersici, and Carcharhinus amboinensis. Our investigation underscores species with urgent conservation needs and reduces data deficiencies. These data will inform and pivot future scientific and conservation efforts to protect remaining populations of some of the most vulnerable Chondrichthyes in the Arabian Seas Region.